Excerpts from "City Disappearing" - Brown, Kathleen (UnderCurrents: Journal of Critical Environmental Studies, 2017)
The flood came while they were in bed, rain drops on the windows refracted the city lights on their covers. Their bodies were turned away from one another, the storm chucked torrents but the fight they had the night before was heavier water in the room... ...... Find full piece in .pdf below.